Evaluation of Protective Activity of Curcumin in Reducing Methotrexate Induced Liver Cells Injury: An Experimental Study on Iraqi White Domestic Rabbits (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: Hepatotoxicity is a common problem in medical practice, most of the commonly used drugs are potentially hepatotoxic. Although Methotrexate is a hepa- toxic drug, it is widely used in the treatment of many cancerous and non-cancerous conditions because of its cytotoxic and immunosuppressant activity. Curcumin con- tains a variety of natural substances with antioxidant properties, it is widely used in  folk medicine.Antioxidant activity of Curcumin can reduce liver cell injury induced by Methotrexate administration.Objective: The research aims to study the methotrexate hepatoxicity on rabbits, and the hepatoprotective activity of Curcumin.Materials and Methods: Thirty white domestic rabbits were bought from animal market and grouped randomly into three groups; control group received intraperitoneal normal saline, methotrexate group received 6.5 mg/Kgm body weight intraperitoneal methotrexate, and curcumin group received oral Curcumin in addition to intraperitoneal methotrexate.Results: The study showed abnormal liver function tests, INR, liver tissues oxida- tive markers, and liver cell injury on histopathology in Methotrexate group, and normal findings in Curcumin groups.Conclusion: It is concluded that the Methotrexate is a hepatotoxic drug. The results also shoe that the concomitant administration of Curcumin reduced hepatotoxicity.Recommendation: It is recommended to use of Curcumin in clinical practice as a food supplement to patient receiving methotrexate to reduce hepatotoxicity.